CEMAsuite: open source degenerate PCR primer design. (20th July 2015) - Lane, Courtney E.; Hulgan, Daniel; O'Quinn, Kelly; Benton, Michael G.
Abstract : Summary: The codon-equivalent multiple alignment suite begins conservational analysis for polymerase chain reaction primer design at the protein level, allowing the user to design consensus primers capable of detecting homologous coding sequences even when low-to-moderate sequence information is available. This package also condenses the wealth of information associated with multiple sequence alignments and presents them in an intuitive manner, allowing the user to quickly and effectively address degenerate primer design considerations. Availability and implementation: https://sourceforge.net/projects/cemasuite/ . Contact: benton@lsu.edu or cemasuite@gmail.com Supplementary information: Supplementary data are available at Bioinformatics online.